Complete ablation rate of percutaneous radiofrequency ablation of hepatocellular carcinoma in favorable and unfavorable locations: using real time ultrasound guidance and expandable electrode needle - Inmutto, Nakarin; Srisuwan, Tanop; Kattipatanapong, Thanate; Kaoworakarn, Chinnu (Biomedical Sciences and Clinical Medicine, 2018)
Objective To evaluate the success rate of percutaneous radiofrequency ablation (RFA) for hepato-cellular carcinoma (HCC) by using real time ultrasound guidance and expandable electro. Methods A retrospective study reviewed of CT and MRI fi ndings from August 2015 to October 2016 of 91 HCCs. The patient’s data, RFA data, location of the HCC, complication after procedure and imaging success rate of complete ablation were analyzed. The size of tumor range 0.5-4.5 cm. We performed RFA by using real time ultrasound guidance and expandable electrode needle (LeVeen, Boston scientifi c cooperation, USA) with stepwise method and double ablation method to reduce ablation time and more ablative area. The unfavorable locations of tumor (exophytic appearance, near capsule, near gallbladder, near bowel, near vessels) were performed without artifi cial ascites. Results Complete ablation was obtained in 91.2% (83/91) of all HCCs. The complete ablation rate in favorable location was 100% (12/12), while the complete ablation rate in unfavorable location was 89.9% (71/79). Only one complication was found in 91 sessions of all HCCs. Conclusion Using expandable electrode catheter combined with real time ultrasound guidance help ablates tumor in high risk locations with high success rate, low complication and fast operation time.